HUBUNGAN ANTARA KECERDASAN EMOSI DAN NILAI SOSIAL TERHADAP TEKANAN DALAM KALANGAN PELAJAR DI SEKOLAH MENENGAH KEBANGSAAN SEPAGAYA, LAHAD DATU, SABAH - Ahmad Muldjamil, Nur Fathiah Faezah; Kamarul Arifain, Siti Marhamah (Jurnal 'Ulwan, 2023)
Low emotional intelligence and lack of appreciation of social values will cause stress in students. This study was conducted to examine the relationship between emotional intelligence and social values against stress among students at Sekolah Menengah Kebangsaan Sepagaya, Lahad Datu, Sabah. A total of 30 male and female students consisting of Form 4 and 5 students were surveyed using the Adolescent Stress instrument, the Malaysian Emotional Intelligence Instrument - Adolescent (IKEM-R) and the Adolescent Social Value Instrument (INS). Data were analyzed descriptively based on mean, t-test, correlation and ANOVA using Statistical Packages For Social Sciences (SPSS) version 26. The results of the study showed that there was no significant relationship between emotional intelligence and stress among Form 4 and 5 students r=.330, >.05. In addition, there is no significant relationship between Social Values and Stress among Form 4 and 5 students r=.330, >.05. Likewise, there is no difference between male and female genders to determine the level of stress of Form 4 and 5 students. In conclusion, the stress level of Form 4 and 5 students at SMK Sepagaya is in a medium level so that it does not interfere with their emotional intelligence and social values.